Angels at the table [compact disc, unabridged] a Shirley, Goodness and Mercy Christmas story - Macomber, Debbie (Random House Audio, 2012)
Shirley, Goodness, and Mercy know that an angel's work is never done, and with Will, an apprentice angel under their wings, they descend upon Times Square in New York City eager to join in the festivities. When Will spies two lonely strangers in the crowd, he decides it's the perfect time to lend a heavenly helping hand. In a strange twist of fate, the angels cook up a brilliant plan to create an unforgettable Christmas miracle.